SISTEM MONITORING BERAT DAN SUKROSA PADA ROYAL JELLY BERBASIS INTERNET OF THINGS - Monifa Arini; Panca Mudjirahardjo; Eka Maulana (Jurnal Mahasiswa TEUB, 2022)
Royal jelly is one type of bee product that has many benefits and high nutritional content. The characteristics of royal jelly are classified as easily damaged if the queen cup is left open for a long time, so the quality of the royal jelly produced is not good. Poor quality will affect the important ingredients in royal jelly which can reduce the amount of royal jelly production. Unfortunately, the harvesting tools used today do not have measurements and monitoring of the composition of weight and royal jelly that support it. Therefore, the purpose of this research is to design a monitoring system for weight and sucrose in royal jelly based on the Internet of Things. The system is equipped with accurate measurement of sucrose content, measurement of harvest weight, and real-time data transmission that is stored through the database. Measurement of sucrose level monitoring was carried out using the TCS-230 sensor resulting in an error percentage of 3.002% and was in accordance with ISO standards. In addition, the results of the measurement of the first harvest weight of 26.2 grams then increased until the fifth harvest, which was 113.2 grams. With Internet of Thingsbased monitoring, the value of sucrose content, weight, time, and date that can be seen through the android application aims to make it easier for users to view incoming realtime data and automatically recap data.Keywords: Royal Jelly, Sucrose, Weight, Internet of Things.